Visual Branding S&N Farm Melalui Desain Logo - Sonhaji Arif (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2021)
Explores the key role of logo design in developing a strong and effective brand identity, particularly in the context of agricultural businesses, as analyzed for S&N Farm. Adopting design thinking as the main approach, this research identifies the critical steps to achieve successful visual branding. The initial stage of research involved a deep understanding of S&N Farm's values and unique identity through the Empathy stage. This laid the foundation for designing a logo design that accurately reflected the company's essence. The Ideation stage brought out a high level of creativity, involving brainstorming and collaboration between the design team and management. As a result, a logo design prototype was created as a physical representation of the creative ideas. Furthermore, the research highlights the importance of a continuous iteration process for design improvement. In this case, consumer engagement and market response are key factors in ensuring the design aligns with the changing preferences and dynamics of the business environment. This research shows that logo design is not a static entity; instead, it evolves according to market needs and trends. The success of the logo design is seen in achieving the desired differentiation, distinguishing the S&N Farm brand from its competitors. The appropriate use of aesthetics creates positive visual appeal, arouses consumer attention, and increases brand recognizability. Logo design is not only a visual element, but also a solution generated through iteration and consumer engagement, creating a unique brand identity. This research provides an in-depth look at how logo design can be a key pillar in the development of strong visual branding. This research has relevant practical implications for agricultural companies and similar businesses to adopt a design thinking approach in building a meaningful and effective brand identity in a changing market.